Needs and preferences regarding a mobile application to support diabetic foot self-care - Geysa Santos Góis Lopes; Maria José Lumini Landeiro; Maria Rui Miranda Grilo Correia de Sousa (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To identify the needs and preferences of individuals with type 2 diabetes regarding the functionalities and characteristics for a mobile application to support foot self-care. Method: Qualitative research with 16 individuals diagnosed with type 2 diabetes recruited during clinical care at a university hospital in Porto, Portugal. Data were collected through semi-structured interviews between March and June 2022 and analyzed using inductive content analysis. Results: Three categories and nine subcategories were identified. Categories included informational needs, essential functionalities for foot health self-care, and user-relevant experience. The preference for objective, limited data input, flexible, and customizable applications was an important factor influencing technology engagement. Conclusion: The research highlighted a preference for customizable and flexible applications, aiding nurses in creating solutions that transform care delivery and enhance the quality of life for individuals living with diabetes.